GABAA receptor signaling induces osmotic swelling and cell cycle activation of neonatal prominin+ precursors - Cesetti, Tiziana; Fila, Tatiana; Obernier, Kirsten; Bengtson, C. Peter; Li, Yuting; Mandl, Claudia; Hölzl-Wenig, Gabriele; Ciccolini, Francesca (Stem cells, 2011)
Signal-regulated changes in cell size affect cell division and survival and therefore are central to tissue morphogenesis and homeostasis. In this respect, GABA receptors (GABAARs) are of particular interest because allowing anions flow across the cell membrane modulates the osmolyte flux and the cell volume. Therefore, we have here investigated the hypothesis that GABA may regulate neural stem cell proliferation by inducing cell size changes. We found that, besides neuroblasts, also neural precursors in the neonatal murine subependymal zone sense GABA via GABAARs. However, unlike in neuroblasts, where it induced depolarization-mediated [Ca2+]i increase, GABAARs activation in precursors caused hyperpolarization. This resulted in osmotic swelling and increased surface expression of epidermal growth factor receptors (EGFRs). Furthermore, activation of GABAARs signaling in vitro in the presence of EGF modified the expression of the cell cycle regulators, phosphatase and tensin homolog and cyclin D1, increasing the pool of cycling precursors without modifying cell cycle length. A similar effect was observed on treatment with diazepam. We also demonstrate that GABA and diazepam responsive precursors represent prominin+ stem cells. Finally, we show that as in in vitro also in in vivo a short administration of diazepam promotes EGFR expression in prominin+ stem cells causing activation and cell cycle entry. Thus, our data indicate that endogenous GABA is a part of a regulatory mechanism of size and cell cycle entry of neonatal stem cells. Our results also have potential implications for the therapeutic practices that involve exposure to GABAARs modulators during neurodevelopment.